2013
DOI: 10.1021/ja405244v
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Crowding Drives Active Pin1 into Nonspecific Complexes with Endogenous Proteins Prior to Substrate Recognition

Abstract: Proteins and nucleic acids maintain the crowded interior of a living cell and can reach concentrations in the order of 200-400 g/L which affects the physicochemical parameters of the environment, such as viscosity and hydrodynamic as well as nonspecific strong repulsive and weak attractive interactions. Dynamics, structure, and activity of macromolecules were demonstrated to be affected by these parameters. However, it remains controversially debated, which of these factors are the dominant cause for the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 57 publications
9
100
1
1
Order By: Relevance
“…S3), suggesting that the intracellular environment remains unperturbed. However, it is apparent, from the NMR spectral features, that the underlying quinary encounters are short-lived and diffusive, in agreement with previous observations (5,37,38,50). As the correlations in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…S3), suggesting that the intracellular environment remains unperturbed. However, it is apparent, from the NMR spectral features, that the underlying quinary encounters are short-lived and diffusive, in agreement with previous observations (5,37,38,50). As the correlations in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…When folded proteins engage in transient intracellular interactions they often respond as single entities and display uniform degrees of signal attenuations. 177,182,183,826 By contrast, transient interactions of disordered proteins often elicit line broadening of few residues only. 151,184,185 In many instances, these effects identify weakly interacting proteins regions.…”
Section: Theoretical and Experimental Methods To Study Idpsmentioning
confidence: 99%
“…In X. laevis oocytes and extracts, Luh et al (45) showed that a peptidyl-prolyl isomerase (Pin1) interacts nonspecifically with the environment through the N-terminal Trp-Trp-binding module (WW) domain. Interestingly, upon substrate recognition, the nonspecific interactions between the WW domain and the environment are lost, and both specific and nonspecific interactions are abrogated when Pin1 contains a mutation that mimics phosphorylation of the WW domain (Fig.…”
Section: Effects Of Crowding On Folding and Weak Interactionsmentioning
confidence: 99%